2005
DOI: 10.1002/imhj.20056
|View full text |Cite
|
Sign up to set email alerts
|

Gender and patterns of emotional availability in mother–toddler and father–toddler dyads

Abstract: Recent research has revealed gender differences in emotional communication and affect regulation during early mother-child interactions that are consistent with later gender differences in relational behavior. The current study extends those findings to father-child interactions. Parent-toddler dyads were videotaped during quiet indoor play when the toddlers were 19 and 24 months old. The observations were coded with Biringen, Robinson, and Emde's (1998) Emotional Availability scales (3rd ed.), which yields sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
123
4
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(158 citation statements)
references
References 57 publications
21
123
4
5
Order By: Relevance
“…The finding that mothers were more sensitive than fathers is in line with findings of previous studies (Lovas 2005;Volling et al 2002). Mothers are often the primary caregiver and therefore they are more familiar with the signals of the child which may make them more sensitive than fathers, see Hallers-Haalboom et al (2014).…”
Section: Discussionsupporting
confidence: 84%
“…The finding that mothers were more sensitive than fathers is in line with findings of previous studies (Lovas 2005;Volling et al 2002). Mothers are often the primary caregiver and therefore they are more familiar with the signals of the child which may make them more sensitive than fathers, see Hallers-Haalboom et al (2014).…”
Section: Discussionsupporting
confidence: 84%
“…Researchers have shown that gender could be a critical factor in relationships formed with adults. Thus as Lovas (2005) reported similar findings were obtained from mothers and fathers which means both parties were found to be more sensitive with their daughters than their sons. Similarly daughters were found to be more responsive and involved during interactions with their mothers and fathers compared to sons.…”
Section: Research Significance(çalişmanin öNemi̇)supporting
confidence: 73%
“…Compared to earlier researches, this finding seemed to have contradictory results especially in terms of parent's perception and gender. For example, Lovas (2005) has found that both mothers and fathers are more sensitive with daughters than with sons, and daughters are more responsive and involved in their relationships both with mothers and fathers than sons. Similarly Colarossi and Eccles (2003) found that boys and girls perceived least support from fathers although they couldn't find any gender differences in perceived support from mothers and teachers.…”
Section: Discussion (Tartişma)mentioning
confidence: 99%
“…It has been applied to mothers as well as fathers (e.g., Atzaba-Poria et al, 2010;Lovas, 2005), generally in free-play settings. The 4th edition of the EA scales (Biringen, 2008) is still relatively new and studies using this edition are only just starting to be published (e.g., Flykt et al, 2012).…”
Section: Emotional Availability Scales (Ea Scales)mentioning
confidence: 99%